Factors Influencing Nurses' Compliance with Patient Safety Policies in Hospital - Yuni Dwi Hastuti; Shofa Chasani; Muhammad Hasib Ardani (NurseLine Journal, 2020)
Patient safety is a global issue and a top priority in hospitals. Incidence of unexpected events varies significantly in Indonesia. Nurses’ compliance is an essential factor in the successful implementation of patient safety policies in hospitals. This study aimed to determine the factors influencing nurses’ compliance with patient safety policies in inpatient units of Dr. Kariadi general hospital, Semarang. This study employed a descriptive correlational design with a cross-sectional approach. The samples were 220 staff nurses recruited using a proportional random sampling technique. The data were collected using a questionnaire developed by the researchers and analyzed using the univariate analysis, Chi-Square test, and multivariate multiple logistic regression test. Results of the bivariate analysis showed that there were effects of supervision (p=0.038; OR=1.828), the character of authority figures (p=0.001; OR=2.648), and non-compliant colleagues (p=0.0001; OR=2.899) on nurses’ compliance with patient safety policies. However, gender (p=0.691), working environment (p=0.891), and contradictory orders (p=0.243) were found to have no effects on nurses’ compliance with patient safety policies. Results of multivariate analysis using a multiple logistic regression analysis showed that non-compliant colleagues were the most influential factor of nurses’ compliance with patient safety policies in the hospital. There were effects of supervision, the character of authority figures, and non-compliant colleagues on nurses’ compliance with patient safety policies. In contrast, gender, working environment, and contradictory orders showed no effects on nurses’ compliance. Non-compliant colleagues had the most effect on nurses’ compliance.